The Effect of Annealing Process on Surface Plasmon Resonances in Tungsten Trioxide Films - H. Mustafa, Mohammed; Aliyah A. Shihab (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
In this study, after pyrolyzing the prepared solution, we made films from transitional tungsten oxide metal doped with gold nanoparticles and deposited them using a spray deposition technique on glass substrates at a substrate temperature of 320°C. We then annealed the prepared films at various temperatures (673,773 K) for one hour, in which we detected the band of localized surface plasmon resonance (LSPR) in gold-doped tungsten oxide films around the wavelength of 595 nm, and thermal treatment increased its intensity to near the wavelength of 580 nm. The produced and annealed thin films also demonstrated an indirect energy gap smaller than (2.86-2.61) eV in the UV-visible spectrum. The structural characteristics of the manufactured and annealed thin films reveal an amorphous structure at the substrate temperature of 320°C, but a polycrystalline structure at the annealing temperature, where researchers discovered monoclinic tungsten trioxide structures. (AFM), which achieved the maximum particle size of 75.93 nm after it was 47.85 nm, allowing researchers to see that the thin film of all the samples has a nanostructure.